The origin of pine pollen grains captured from air at Calypsobyen, Svalbard - Jędryczka, Małgorzata; Żuraw, Beata; Zagórski, Piotr; Rodzik, Jan; Mędrek, Karolina; Pidek, Irena Agnieszka; Haratym, Weronika; Kaczmarek, Joanna; Sadyś, Magdalena (Polish Polar Research, 2023)
Spitsbergen is the largest island in the Svalbard Archipelago (Norway) that has been permanently populated. The harsh Arctic climate prevents development of large vascular plants such as trees. A two-year aerobiological survey was conducted within the framework of two consecutive polar expeditions (2014 and 2015) in Spitsbergen (Calypsobyen, Bellsund). The air quality was measured continuously from June/July to August using a 7-day volumetric air sampler, Tauber trap and moss specimens. Collected air samples and gravimetric pollen deposits were processed following transfer to sterile laboratory conditions and analyzed with the aid of light microscopy. Days when pine pollen grains were detected in the air were selected for further analysis. Clusters of back-trajectories, computed using the Hybrid Single Particle Lagrangian Integrated Trajectory model in combination with ArcGIS software as well as the Flextra trajectory model, showed the movement of air masses to the sampling location at Hornsund, and thus indicated the likely origin of pollen grains. The GlobCover 2009 and CORINE Land Cover 2012 datasets were employed to establish the distribution of coniferous forests in the areas of interest. Conclusions were drawn based on the analyses of the circulation of air masses, using visualization of global weather conditions forecast to supercomputers. For the first time, we have demonstrated that pine pollen grains occurring in pine-free Spitsbergen, could originate from numerous locations, including Scandinavia, Iceland, Siberia and northern Canada. Pollen grains were transported via air masses for distances exceeding 2000 km. Both air samples and gravimetric pollen deposits revealed the same pattern of Pinus pollen distribution.